The Role of Human Resource Management: Strategies Improvement on the Readiness for AEC - Wiriyapipat, Nipa (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The establishment of an ASEAN Economic Community (AEC) makes the organization and private sector in Thailand facing more intense competition. It is necessary for the organization to adjust itself in relevant areas and for people to be well prepared for entering the ASEAN Economic Community, which was officially enforced on December 31, 2015. Hence, personnel working in human resources with full responsibility in workforce management have to play an active role in order to enhance its potential by becoming agents of change. The focus on the matters of AEC blueprint mobility must be followed up closely, such as binding contracts and agreements among ASEAN countries; strengthening the opportunity and its impact affecting the organization, including promoting people, introducing new ideas while, understanding the upcoming changes those will incur. Besides, personnel in human resources have to adjust to the role of a strategic partner. Strategic human resource plans have to be developed in line with the organization's strategic plan and to be integrated into the human resources process in many areas, including human resource planning, recruitment and selection, human resource development, performance appraisal and employee retention. Such steps will enable human resources to increase its competency to reach the degree of international standards, which successfully, lead to the readiness for AEC.